Pipelines 2015 : recent advances in underground pipeline engineering and construction : proceedings of the Pipelines 2015 Conference, August 23-26, 2015, Baltimore, Maryland - Sever, V. Firat; Osborne, Lynn (American Society of Civil Engineers, 2015)
Proceedings of Pipelines 2015, held in Baltimore, Maryland, August 23-26, 2015. Sponsored by the Pipelines Division of ASCE. This collection contains 174 peer-reviewed papers on recent advances in underground pipeline engineering and construction. Topics include: trenchless installation; pipeline planning, design, analysis, and construction; risk and safety assessments; and operation, maintenance, and rehabilitation of pipelines. These papers will be useful to design and consulting engineers, owner agencies and operators, and contractors, manufacturers, and suppliers of pipelines.
Keywords: Pipelines -- Congresses.; elektronické knihy; electronic books